Pathophysiology of diabetes in elderly people - Paolisso, Giuseppe (Acta Biomedica Atenei Parmensis, 2010)
The increasing proportions of older persons accounting for global populations, and the implications for increasing rates of chronic diseases such as type 2 diabetes mellitus, continue to be a cause of concern for clinicians. Considering that older persons are a very heterogeneous group of individuals, the management of type 2 diabetes is particularly challenging. Once type 2 diabetes is diagnosed, the principles of it’s management are similar to those in younger patients, but with special considerations linked to the increased prevalence of comorbidities and relative inability to tolerate adverse effects of medication and hypoglycemia. In addition, there are clinical aspects complicating diabetes care in the elderly including cognitive disorders, physical disability and geriatric syndromes, such as frailty. Available anti-diabetic oral drugs include insulin secretagogues (meglitinides and sulfonylureas), biguanides (metformin), a-glucosidase inhibitors, thiazolidinediones (TZDs) and newly introduced glucagon-like peptide-1 (GLP-1) analogues and inhibitors of GLP-1 degrading enzyme dipeptidyl peptidase-4 (DPP-4). Unfortunately, as type 2 diabetes progresses in older persons, polypharmacy intensification is required to reach adequate metabolic control with the risk of adverse effects due to age-related changes in drug metabolism. The present review discusses the European Diabetes Working Party guidelines for type 2 diabetes in older persons with and without frailty and their importance on preventing or at least slowing down diverse aspects of disability.